Amenability testing of fine coal beneficiation using laboratory flotation column - Park, C.; Subasinghe, Nimal; Han, O. (Japan Institute of Metals (JIM), 2015)
The amenability of beneficiating a low rank coal has been studied using a laboratory CPT CoalPro flotation column. After review of the published literature various relationships between bubble size and superficial gas rate, bubble surface area flux and gas hold up and slip velocity and bubble size have been deduced in relation to the coal slurry and compared with relationships reported in the literature. A performance curve for the flotation column tested under the operating conditions revealed that the optimal size range of coal that yields optimal separation occurred in the size range 60–200 microns. Empirical relationships a) to estimate the gas hold up in terms of the measurable quantities, such as superficial gas and water flow rates and frother concentration and b) to predict the carrying capacity of particles of various sizes into the concentrate have been developed. Based on grade/recovery plots, the optimal separation that can be achieved for the given coal in a flotation column was found to be 85% combustible recovery with 81% ash rejection at the separation efficiency of 62% along with the corresponding operating conditions. Empirical relationships to predict the recovery of combustibles and ash rejection in terms of operating variables have also been proposed.